Renal resistive index of adult healthy dogs submitted to short-term whole-body vibration exercise - Freire, Livia [UNESP]; Rahal, Sheila Canevese [UNESP]; Dos Santos, Ivan Felismino Charas [UNESP]; Teixeira, Carlos Roberto [UNESP]; Inamassu, Leticia Rocha [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Science Alert, 2015)
Exercises involving whole-body vibration are useful for stimulation and physical rehabilitation. However, it is necessary to verify its effects not only on musculoskeletal tissues but also on internal organs. This study aimed to investigate the influence of the whole-body vibration platform on the renal resistive index in healthy dogs. Ten clinically healthy dogs of different breeds, 6 males and 4 females, aged from 1.7-3.5 years (mean 2.1±0.6 SD) and weighing from 20.5-41 kg (mean 32.1±7.1 SD), were used. The dogs were submitted to one session on a whole-body vibration platform (Thera Plate) at 30 Hz frequency for 5 min, followed by 50 Hz for 5 min and finishing with 30 Hz for 5 min. The renal artery resistive index of the left kidney was measured before and immediately after the whole-body vibration platform session, using a spectral doppler ultrasound (Triplex doppler imaging). The mean resistive index values before and immediately after the session were 0.65 (±0.04 SD) and 0.63 (±0.05 SD), respectively. In conclusion, the resistive index is not altered by a single whole-body vibration session using the TheraPlate platform.
Keywords: Blood urea nitrogen; Canine; Complete blood count; Doppler ultrasound; Serum total protein; Vibration plate